Ultraspeed synthesis of highly fluorescent N‐doped carbon dots for the label‐free detection of manganese (VII). Issue 8 (22nd February 2021) - Mohammed, Areef; Gugulothu, Yaku; Bandi, Rajkumar; Dadigala, Ramakrishna; Utkoor, Umesh Kumar
Abstract: Here, we report ultraspeed preparation of highly emissive nitrogen‐doped carbon dots (NCDs) using threonine and guanidine hydrochloride by the microwave irradiation method. Experimental conditions such as microwave power, irradiation time, and reactant ratio were varied to achieve high‐quality NCDs. NCDs were thoroughly characterized using transmission electron microscopy, X‐ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, UV–visible spectroscopy, and fluorescence spectroscopy. NCDs presented high aqueous solubility, bright emission with a quantum yield of 30%, and excitation‐dependent emission. Investigation of optical properties unveiled their admirable characters of tolerance to photobleaching, high salinity, pH, and long shelf life. Evaluation of their metal ion detection ability unveiled their selective fluorescence quenching response to Mn (VII), and further explorations revealed the application of NCDs as a label‐free probe for Mn (VII) detection. The probe presented a good linear response ( R 2 = 0.992) in the concentration range of 5–35 μM with a detection limit of 0.66 μM. Mechanistic studies disclosed that the inner filter effect was responsible for fluorescence quenching. The probe presented no significant interference and was successfully applied for the quantification of Mn (VII) in spiked real‐water samples. Abstract : Here, we report a 1‐min preparation of highly emissive NCDs using threonine and guanidine hydrochloride by the microwave irradiation method. These NCDs used as a label‐free probe for Mn (VII) detection, and the probe presented a good linear response in the concentration range of 5–35 μM with a detection limit of 0.66 μM.